DEVELOPMENT POLICY OF INTERACTION WITH EXTERNAL ENTITIES IN THE SYSTEM OF DEVELOPMENT OF LOGISTICS ACTIVITY OF THE ENTERPRISE - SAVIN, STANISLAV; DZHERELIUK, YULIIA; VOSKRESENSKA, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is provided a critical analysis of the current state and problems of logistics activities of enterprises The theoretical basis of the study was a number of publications of economists, which analyzed the conceptual foundations of the concept of logistics, logistics activities of the enterprise, substantiated its role in ensuring the effective functioning and development of modern enterprise. It is summarized that the company as it conducts business operations encounters a large number of external entities, which together form the demand for products, to some extent determine the financial results and opportunities for business. The essence and features of the development of logistics activities of enterprises are determined. Views on cost management by different scholars are analyzed. It is determined that well-known enterprises from developed countries of the world observe a disproportionately high increase in the share of marketing and sales costs compared to the increase in sales. It is generalized that the main goal of logistics cost management is to find the most efficient way to use the available limited logistics resources. Recommendations for reforming logistics processes have been formed. Theoretical provisions and practical recommendations for improving the interaction with external actors in the system of development of logistics activities of the enterprise are substantiated. The strategic grouping of consumers of the enterprise according to the profile of their profitability for the enterprise is carried out. A strategy of interaction with consumers of different categories has been developed. The characteristics and features of suppliers that are necessary to optimize the logistics activities of the enterprise are summarized. It is determined that the improvement of the system of information support of management processes is one of the conditions for improving the quality of logistics activities of the enterprise.
Keywords: development policy; logistics activities; enterprise; cost management; consumer